Supplement (Zeszyty Teoretyczne Rachunkowości)
SupplementIn the article: Magdalena Kowalczyk, Robotic Process Automation in accounting for public sector entities from the perception of clerks – evolution or revolution? Zrobotyzowana automatyzacja procesów w księgowości jednostek sektora publicznego w opinii urzędników – ewolucja czy rewolucja? published in “Zeszyty Teoretyczne Rachunkowości” 2024, Vol. 48, No. 3, pp. 197–214, https://doi.org/10.5604/01.3001.0054.7263 the following information was not included:Research fundingThe research was subsidized with funds from the Ministry of Science awarded under the “Regional Excellence Initiative” programme for the project “Poznań University of Economics for the Economy 5.0: Regional Initiative – Global Effects (IREG)”.